Systems thinking in COVID-19 recovery is urgently needed to deliver sustainable development for women and girls - Omukuti, Jessica; Barlow, Matt; Giraudo, Maria Eugenia; Lines, Tallulah; Grugel, Jean (The Lancet Planetary Health, 2021)
In low-income and middle-income countries, such as those in sub-Saharan Africa and Latin America, the COVID-19 pandemic has had substantial implications for women’s wellbeing. Policy responses to the COVID-19 pandemic have highlighted the gendered aspect of pandemics; however, addressing the gendered implications of the COVID-19 pandemic comprehensively and effectively requires a planetary health perspective that embraces systems thinking to inequalities. This Viewpoint is based on collective reflections from research done by the authors on COVID-19 responses by international and regional organisations, and national governments, in Latin America and sub-Saharan Africa between June, 2020, and June, 2021. A range of international and regional actors have made important policy recommendations to address the gendered implications of the COVID-19 pandemic on women’s health and wellbeing since the start of the pandemic. However, national-level policy responses to the COVID-19 pandemic have been partial and inconsistent with regards to gender in both sub-Saharan Africa and Latin America, largely failing to recognise the multiple drivers of gendered health inequalities. This Viewpoint proposes that addressing the effects of the COVID-19 pandemic on women in low-income and middle-income countries should adopt a systems thinking approach and be informed by the question of who is affected as opposed to who is infected. In adopting the systems thinking approach, responses will be more able to recognise and address the direct gendered effects of the pandemic and those that emerge indirectly through a combination of long-standing structural inequalities and gendered responses to the pandemic.
Keywords: 2000 à aujourd'hui; 2010-2019; 2020-2029; afrique; afrique subsaharienne; amérique latine; amériques; approches et analyses; environnement; justice climatique; justice sociale; pandémie; patriarcat; politiques publiques; projet charge mentale; périodes historiques; racisme; régions géographiques; santé; santé publique; sexisme; systèmes d'oppressions; thématiques

Cohabiter avec le navettage aéroporté / Expériences de femmes et de communautés de la Côte-Nord (2021)
Regroupement des femmes de la Côte-Nord « Cohabiter avec le navettage aéroporté / Expériences de femmes et de communautés de la Côte-Nord » Présentation dans le cadre du webinaire "Recherche collaborative et diversité des réalités régionales", organisé par la communauté de pratique "Nouvelles-Alliances pour plus de savoirs en égalité des sexes".
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; approches et analyses; groupes communautaires; groupes de femmes; inégalités; justice sociale; outils; périodes historiques; québec; recherche en milieux de pratique; relais-femmes; ressource en ligne; régions géographiques; systèmes d'oppressions; thématiques; travail

Capire - Portail international de communication féministe (Capire, 2021)
Des voix féministes pour changer le monde! Capire est un portail international de luttes féministes, populaires, anticapitalistes et antiracistes. Capire est un outil de communication créé en 2021 pour faire écho aux voix des femmes en mouvement, rendre visibles les luttes et les processus organisationnels dans les territoires et renforcer les références locales et internationales du féminisme populaire, anticapitaliste et antiraciste. Capire signifie « comprendre ». Par les regards et les voix des femmes, nous comprenons le monde. Avec le féminisme nous le transformons ! Le nom Capire reprend la chanson de lancement de la Marche Mondiale des Femmes, en 2000, chantée en 24 langues par des femmes de différentes parties du monde. Nous produisons et articulons des interviews, des analyses, des rapports d’expériences et d’expressions culturelles de femmes qui, aux quatre coins du monde, résistent et se transforment. Les textes et les supports multimédias de Capire sont organisés en six axes thématiques : mouvement, économie féministe, justice environnementale, souveraineté alimentaire, démilitarisation et autonomie. Ces axes guident la radicalité de notre combat politique, de notre contenu et de notre identité visuelle.
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; approches et analyses; justice sociale; marche mondiale des femmes; militance; périodes historiques; rapports sociaux de sexe; thématiques; écoféminisme

Guérison Collective Healing - Yuen, Felice; Gabriel, Wanda; Fast, Elizabeth (Guérison Collective Healing, 2021)
Aborder les expériences des femmes autochtones dans les prisons provinciales du Québec Vers une guérison collective Addressing the experiences of Indigenous women in Quebec’s provincial prison Towards Collective Healing
Keywords: 2000 à aujourd'hui; 2010-2019; 2020-2029; amériques; approches et analyses; canada; communauté; cours; discipline; droits des femmes*; droits des femmes* autochtones; histoire et politique; intersectionnalité; justice sociale; militance; pol4105; premier cycle; périodes historiques; régions géographiques; santé; sciences humaines; sciences sociales; sexisme; système carcéral; système colonial; systèmes d'oppressions; thématiques; travail social; violences